Neuromuscular effects of venoms and crotoxin-like proteins from Crotalus durissus ruruima and Crotalus durissus cumanensis - Garrido Cavalcante, Walter Luis [UNESP]; Ponce-Soto, Luis Alberto; Marangoni, Sergio; Gallacci, Marcia [UNESP] (Elsevier B.V., 2015)
A myographic study was performed to compare the neuromuscular effects of venoms and crotoxin-like proteins from Crotalus durissus ruruima and Crotalus durissus cumanensis in mice phrenic-diaphragm preparation. It was concluded that both venoms present neurotoxic activity as a consequence of their crotoxin content. Furthermore, crotoxin from C.d. cumanensis is more potent than that from C.d. ruruima venom. At the concentration range in which both venoms express neurotoxic activity, only C.d. cumanensis venom also manifest a direct myotoxic effect that probably involves the synergic participation of other components than crotoxin. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Snake venom; Neurotoxin; Neuromuscular transmission; Crotalus subspecies